Das spätantike Rom und die stadtrömische Senatsaristokratie (395-455 n. Chr.) Eine althistorisch-archäologische Untersuchung - Wagner, Hendrik (Millennium-Studien / Millennium Studies, 2021)
This study inquires into the political and social significance ascribed to the urban Roman senatorial aristocracy and the senate in the first half of the fifth century CE. This volume therefore examines a topic of central significance in the history of the Roman West and Christianization, connecting research perspectives from ancient history and archaeology.